In-depth circulating tumor DNA sequencing for prognostication and monitoring in natural killer/T-cell lymphomas - Kim, Jin Ju; Kim, Hyun-Young; Choi, Zisun; Hwang, So yoon; Jeong, Hansol; Choi, Jong Rak; Yoon, Sang Eun; Kim, Won Seog; Kim, Sun-Hee; Kim, Hee-Jin; Shin, Sang-Yong; Lee, Seung-Tae; et al. (Frontiers in Oncology, 2023)
Background: Epstein–Barr virus (EBV) quantitation and current imaging modalities are used for diagnosis and disease monitoring in Extranodal NK/T cell lymphoma (ENKTL) but have limitations. Thus, we explored the utility of circulating tumor DNA (ctDNA) as a diagnostic biomarker. Methods: Through in-depth sequencing of 118 blood samples collected longitudinally at different time points from 45 patients, we examined the mutational profile of each sample, estimated its impact on the clinical outcome, and assessed its role as a biomarker in comparison with EBV DNA quantitation. Results: The ctDNA concentration was correlated with treatment response, stage, and EBV DNA quantitation. The detection rate of ctDNA mutation was 54.5%, with BCOR (21%) being the most commonly mutated gene in newly diagnosed patients; TP53 mutation (33%) was the most prevalent in patients that experienced a relapse. Additionally, patients in complete remission exhibited a rapid clearance of ENKTL-related somatic mutations, while relapsed patients frequently presented with persisting or emerging mutations. We detected ctDNA mutations in EBV-negative patients (50%) and mutation clearance in EBV-positive patients in remission, suggesting ctDNA genotyping as an efficient complementary monitoring method for ENKTL. Additionally, mutated DDX3X (PFS HR, 8.26) in initial samples predicted poor outcome. Conclusion: Our results suggest that ctDNA analysis can be used to genotype at diagnosis and estimate the tumor burden in patients with ENKTL. Furthermore, ctDNA dynamics indicate the potential use of testing it to monitor therapeutic responses and develop new biomarkers for precision ENKTL therapy.